Genealogical Critique of Institutionalising ‘Inclusive Education’ in Indonesia - Tschapka, Johannes; Nawangsari, Tri (Emerald Publishing Limited, 2022)
We undertake a genealogical critique to undermine the very noble but hardly questioned implementation of inclusive education in Indonesia, less to identify dubious neo-colonial powers of particular groups, than to deconstruct ill-defined understandings of schooling as a process of ‘normalisation’ of the ‘abnormals’. We approach inclusive classes through Foucault’s concept of Heterotopia, a space which is deviant from the norm. Instead of questioning inclusive education as a heterotopian way of schooling only, we contest regular schooling itself and the power normalisation. Along a second Foucauldian concept of Heterochronia we connect historical insights of seating Indonesian children at a regular school desks in 1920 with the training of children with special needs to be seated in Indonesian disability centres 2020. We argue that ‘normalisation’ as such can hardly be critiqued, because it is an existing social and institutional normality. But taking critique as a conflict between colonial, globalising and even humanitarian forces, enables a Foucauldian analysis of normalising technologies of education and of inclusive education in particular.